2004
DOI: 10.1590/s0100-204x2004001100003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of neem extract on the cotton aphid

Abstract: -The aphid Aphis gossypii Glover (Hemiptera: Aphididae), a harmful pest on cotton, causes direct damage, reducing plant vigor, and indirect damage by honeydew secretion and transmission of several viruses. Due to the problem of pesticide resistance, alternative techniques for chemical control, such as the use of natural insecticides, have been object of research. The effects of aqueous extracts of neem (Azadirachta indica A. Juss) seed powder on the development, survival and fecundity of A. gossypii were evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 18 publications
2
16
0
4
Order By: Relevance
“…De maneira geral, os resultados acima estão de acordo com Santos et al (2004) que, ao estudar a mortalidade de ninfas de A. gossypii, encontraram valores de 60 e 100% nas concentrações de 410 (0,4%) e 1.410 mg por 100 mL (1,4%) de extratos de nim, respectivamente. Breda et al (2010), ao analisar a toxicidade letal de inseticidas botânicos sobre adultos ápteros desse pulgão, obtiveram valores de toxicidade letal baseados em CL 50 , que variaram de 10,15 (1,015%) a 13,37 mL L -1 (1,337%), para produtos à base de nim.…”
Section: Resultsunclassified
“…De maneira geral, os resultados acima estão de acordo com Santos et al (2004) que, ao estudar a mortalidade de ninfas de A. gossypii, encontraram valores de 60 e 100% nas concentrações de 410 (0,4%) e 1.410 mg por 100 mL (1,4%) de extratos de nim, respectivamente. Breda et al (2010), ao analisar a toxicidade letal de inseticidas botânicos sobre adultos ápteros desse pulgão, obtiveram valores de toxicidade letal baseados em CL 50 , que variaram de 10,15 (1,015%) a 13,37 mL L -1 (1,337%), para produtos à base de nim.…”
Section: Resultsunclassified
“…Os efeitos da azadiractina sobre insetos incluem repelência, deterrência alimentar, interrupção do crescimento, interferência na metamorfose, esterilidade e anormalidades anatômicas (Mordue & Nisbet 2000, Martinez & Emden 2001, Ve nzon et al 2007, Santos et al 2004.…”
Section: Palavras-chave: Fungo Entomopatogênico Inseticida Botânicounclassified
“…a mesma espécie, como M. persicae (Verkerk et al 1998, Ve nzon et al 2007. No entanto, de forma geral, o controle exercido pela formulação comercial utilizada neste estudo foi muito superior àquela relatada para extrato de sementes de nim para o controle do pulgão M. persicae (Venzon et al 2007), mas comparável àquela encontrada quando da utilização de extrato aquoso de pó de sementes no controle de A. gossypii (Santos et al 2004), ou de inseticidas à base de nim para o controle de M. persicae e B. brassicae (Verkerk et al 1998). Tabela 5 Efeito de emulsão de óleo de nim (Neemseto ® ) sobre o crescimento, esporulação e viabilidade dos isolados CG 001 de Beauveria bassiana e CG 30 de Metarhizium anisopliae na concentração de 10 7 conídios ml -1 Temp.…”
Section: Seleção De Isoladosunclassified
“…These alkaloids contribute to the general properties of the plant. Different parts of this plant have been used as insecticides and pesticides (Koul et al;dos Santos et al, 2004;Siddiqii et al, 2004;Jin et al, 1995), and have been reported to have inhibitory effects on several ranges of micro-organisms (Talwar et al, 1997;Garq et al, 1998;Baswa et al, 2001;Bocke et al, 2004).…”
Section: Introductionmentioning
confidence: 99%